Report on the second congress fase – 78 Warsaw, September 18–22, 1978 - OZIMEK, E. (Archives of Acoustics, 1979)
The Second Congress FASE, organized by the Institute of Fundamental Technological Research in cooperation with the Polish Acoustical Committee of the Polish Academy of Sciences and the Polish Acoustical Society took place in the conference rooms of the Palace of Science and Culture on 18-22 September. The Congress was sponsored by FASE (Federation of Acoustical Societies of Europe) authorities represented by the president of FASE prof. dr. H. G. DIESTEL, vice-president prof. dr. O. W. van WULFFTEN-PALTHE and FASE secretary dr. F. KOLMER.